2013
DOI: 10.1371/journal.pntd.0002221
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized Study of The Safety of Integrated Treatment of Trachoma and Lymphatic Filariasis in Children and Adults in Sikasso, Mali

Abstract: BackgroundNeglected tropical diseases are co-endemic in many areas of the world, including sub Saharan Africa. Currently lymphatic filariasis (albendazole/ivermectin) and trachoma (azithromycin) are treated separately. Consequently, financial and logistical benefit can be gained from integration of preventive chemotherapy programs in such areas.Methodology/Findings4 villages in two co-endemic districts (Kolondièba and Bougouni) of Sikasso, Mali, were randomly assigned to coadministered treatment (ivermectin/al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…There is also scope for cooperation between mass treatment programs, for example co-administration of ivermectin, albendazole and azithromycin, where more than one treatment is indicated and appropriate safety and efficacy data exist. 26 Our data add to existing data suggesting that yaws is no longer a public health problem in Fiji and that trachoma is not likely to be one of the major causes of blindness in Fiji. Given the mixed findings of trachoma surveys conducted in Fiji early impact assessments should be conducted to guide Ministry of Health trachoma elimination activities.…”
Section: Discussionsupporting
confidence: 67%
“…There is also scope for cooperation between mass treatment programs, for example co-administration of ivermectin, albendazole and azithromycin, where more than one treatment is indicated and appropriate safety and efficacy data exist. 26 Our data add to existing data suggesting that yaws is no longer a public health problem in Fiji and that trachoma is not likely to be one of the major causes of blindness in Fiji. Given the mixed findings of trachoma surveys conducted in Fiji early impact assessments should be conducted to guide Ministry of Health trachoma elimination activities.…”
Section: Discussionsupporting
confidence: 67%
“…They may consider alternatives such as targeted treatment [ 47 ] or biannual treatment [ 8 , 48 ]. There may be substantial cost savings associated with proposed integration of efforts to survey and distribute treatment with programs for other NTDs [ 49 51 ]. Most importantly, we must recognize that in the imperfect context in which programs on the ground operate, adding more annual MDAs without regard to coverage, programmatic continuity, and underlying environmental context will not guarantee trachoma elimination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the long-standing practice of co-administration with albendazole, large-scale studies have now demonstrated the safety of co-administration with azithromycin, opening the possibility of integrating control of scabies with control of yaws and/or trachoma. [128][129][130] Similarly, early analysis of a multi-national safety cohort study of combination therapy of ivermectin, diethylcarbamazine and albendazole (IDA) for lymphatic filariasis did not reveal safety concerns and administration of this combination of agents has now been recommended for specific epidemiological contexts within WHO guidelines. [131][132][133][134] Monitoring for development of resistance of mites to acaricides will also be important.…”
Section: Treatmentmentioning
confidence: 99%